Pengaruh Disiplin Belajar dan Pendapatan Orang Tua terhadap Hasil Belajar Siswa Mata Pelajaran Ekonomi Dengan Motivasi Belajar sebagai Variabel Intervening Dalam Masa Pandemi Covid-19 - Rumi Astuti; Rita Sofyan (Jurnal Salingka Nagari, 2022)
This study aims to determine the effect of learning discipline and parental income on student learning outcomes in economics subjects with learning motivation as an intervening variable during the covid-19 pandemic at SMAN 17 Tebo. This type of research is causative research. The population in this study were all students of SMAN 17 and the determination of the number of samples using the slovin formula was 100 samples. The data used is the type of primary data obtained through the distribution of questionnaires in the form of a google form for students of SMAN 17 Tebo with predetermined criteria. The analytical method used is path analysis using SPSS 21. The results show that (1) learning discipline has a significant and positive effect on learning motivation, (2) parental income has a significant and positive effect on learning motivation, (3) parental income has a significant and positive effect on learning outcomes, (4) learning motivation significant and positive effect on learning outcomes, (5) learning discipline has a significant and positive effect on learning outcomes with learning motivation as an intervening variable, (6) parental income has a significant and positive effect on learning outcomes with learning motivation as an intervening variable.